Integracja europejskiego rynku kapitałowego - szanse i zagrożenia dla polskiego rynku - Banaszczak-Soroka, Urszula (European Capital Market Integration - Opportunities and Threats for the Polish Market, 2008)
Integration of the EU capital markets opens new opportunities for issuers and investors and at the same time intensifies competition among institutions which form the institutional infrastructure of those markets. Polish exchange market was chosen by over a dozen foreign issuers as a quotation place, which has had a significant impact on the Warsaw Stock Exchange capitalization. Several companies enjoy a remote member status. Investors are able to purchase units of numerous investment funds. Being in such position, the Warsaw Stock Exchange is perceived as the most resilient in Eastern Europe and against it, institutions like Polish investment companies or investment funds may be said to be sluggish in taking advantage of common passport principle.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 56-67